PENGARUH PENAMBAHAN GLISEROL PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA (Oreochromis niloticus) [Effect of Glycerol Addition into Fish Feed on the Growth and Survival Rate of Nile Tilapia (Oreochromis niloticus)] - Suryaningrum, Lusi Herawati; Mulyasari, Mulyasari; Samsudin, Reza (Research Center for Biology-Indonesian Institute of Sciences, 2017)
The aim of this research was to determine the optimum percentage of glycerol addition into the diets of Nile Tilapia (Oreochromis niloticus) on growth performance, feed convertion ratio, and survival rate. The research was conducted using 15 aquaria with the size of 60 x 50 x 45 cm3, each containing 25 O. niloticus with average initial weight of 4.63 ± 0.15 g. The experiment was conducted using a complete random design with five treatments and three replications. Isonitrogenous (31%) and isocaloric (17 MJ.kg-1) diets were provided for 60 days of rearing period. Five diets were formulated with glycerol content of 0% (G0); 5% (G5); 10% (G10); 15% (G15), and 20% (G20). Fish were fed twice daily with experimental diet at satiation level. The result showed that addition of 10% glycerol in the diet (G10) presented the highest values for weight gain (105.85 ± 0.40%), specific growth rate (3.44 ± 0.01%), protein retention (27.75 ± 0.02%), protein efficiency ratio (2.53 ± 0.15%), lipid retention (60.44 ± 0.03%), and feed convertion ratio (1.59 ± 0.01%) (P < 0.05). Survival rate was not affected by dietary containing glycerol (P > 0.05). Therefore, addition of 10% glycerol into the diet gave a significant increase on growth performance and feed convertion ratio without adverse effect on survival rate of Nile Tilapia.